TARGETING ANGIOGENESIS WITH FLUPHENAZINE-ZINC OXIDE NANOCONJUGATES: A POTENTIAL MECHANISM FOR IMPROVING ANTIPSYCHOTIC EFFICACY - DASARI, NAGASEN; BALLA, SUJIYA; KONDRAPU, PYDIRAJU; GUMMADI, RAMAKRISHNA; SURADA, NOOKARAJU; KONDRU, UMA MAHESWARI; PINDIPROLU, SAI KIRAN S. S. (International Journal of Applied Pharmaceutics, 2023)
Objective: This study aimed to develop a more effective formulation of Fluphenazine (FLP) for the management of psychosis. Antipsychotics are widely used for the treatment of severe mental disorders such as schizophrenia and bipolar disorder. However, their clinical use is limited due to various side effects and low efficacy in a large number of patients. Nanoparticle-based drug delivery systems have shown great potential in improving the pharmacokinetics and pharmacodynamics of various drugs, including antipsychotics. Zinc oxide nanoparticles (ZnO NPs) have emerged as a promising carrier for drug delivery due to their unique physicochemical properties, biocompatibility, and low toxicity. Methods: In this study, we reported the preparation and characterization of FLU-encapsulated ZnO NPs (FLU-ZnO-NPs) for the management of psychosis. The synthesized FLU-ZnO-NPs were characterized using various techniques, such as X-Ray Diffractometer, Energy Dispersive X-Ray analysis, Transmission Electron Microscopy, and Zetasizer (Malvern). Results: The characterization results showed that the synthesized FLU-ZnO-NPs had improved solubility, enhanced bioavailability, targeted delivery, and reduced toxicity. Conclusion: The development of FLU-ZnO-NPs could provide a more effective and safe treatment option for patients with mental disorders.